Ethical Challenges Faced by Nurses in Oncology Care During Breaking Bad News: A Qualitative Study: Ethical Challenges Faced by Nurses - Qayyum , Adeela; Kousar, Samina; Farooqi, Samina; Kalsoom, Tahira; Kousar, Saima; Sattar, Fouzia (Pakistan Journal of Health Sciences, 2023)
The emphasis of this paper is on the ethical challenges faced by nurses who broke bad news and worked in a tertiary care hospital in Punjab, Pakistan, with patients who were diagnosed with cancer. Objective: To explore the Ethical challenges faced by nurses in oncology care during breaking bad news. Methods: A qualitative phenomenological research design was employed. From the Oncology Department, 15 nurses with at least one year of experience were chosen as a sample. The University of Health Sciences in Lahore served as the study's setting. The Jinnah and Mayo Hospitals in Lahore, Pakistan, Oncology Departments were used to collect the data. Using an interview guide, semi-structured, in-depth face-to-face interviews were conducted to collect data. Thematic analysis framework approach was used to analyses the data that had been gathered. Results: The study's conclusions showed that nurses typically steer clear of BBN because of ethical issues. Conclusions: To give nurses sound knowledge and competence of BBN at the institutional level, capacity building and ongoing nursing education programmes must be set up.